Improving livelihood of farmers through introduction of parasitic control and mineral mixture supplementation in animal - Chakrabarti, Asit; Naskar, Soumen; Kumar, Priya Ranjan; Yadav, V K; Maurya, Sudarshan; Kumari, Sonal; Roy, Shriman Kumar; Singh, Arun Kumar; Bhatt, B P; Das, Bikash (Indian Farming, 2020)
nutritional security. Backyard animal husbandry contributes substantially and has the potential to transform rural economy by upscaling from backyard to sustainable homestead enterprises and for entrepreneurship development of rural unemployed youth. It may also play a role in social mainstreaming. Although it plays an important role in agriculture-led economy of the state, the per capita availability of milk, meat and egg is less than half of the national average. General backwardness and poor productivity of animal husbandry sector in Jharkhand reflected by the fact that per capita availability of milk in Jharkhand is 165 g/ day against national availability of 175 g/day whereas ICMR recommendation is of 400 g/ day. The annual per capita recommendation for egg consumption is 180 while availability in Jharkhand is mere 15 eggs/year against national average of 69 eggs/year. Under the Farmers First Project being implemented by ICAR Research Complex for Eastern Region, Research Centre, Ranchi, technology demonstration on area specific chelated mineral mixture and management of endo- and ecto-parasites in livestock and poultry was initiated for improving the productivity of animals. The action began with sensitization of the farmers towards modern management practices of livestock through Animal health camps followed by training of farmers in each village.